2011
DOI: 10.1074/jbc.m110.125567
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A (SP-A)-mediated Clearance of Staphylococcus aureus Involves Binding of SP-A to the Staphylococcal Adhesin Eap and the Macrophage Receptors SP-A Receptor 210 and Scavenger Receptor Class A

Abstract: There is limited knowledge about host factors that facilitate eradication of Staphylococcus aureus infection in the lung. Methicillin-resistant S. aureus has remained a major cause of hospital-and health care-associated pneumonia since its appearance over 40 years ago and has recently become a more prominent etiology in community acquired pneumonia. Colonization of nasal epithelium with S. aureus, a normal occurrence in over 20% of the population, increases the risk for the development of staphylococcal pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 107 publications
3
90
0
Order By: Relevance
“…The function of SR-A in human and mouse DCs and macrophages in response to Gram-negative and Gram-positive bacteria has been investigated, showing that SR-A functionally contributes to phagocytosis of those bacteria (37,38). Moreover, many studies showed that SR-A plays a significant role in the phagocytosis of S. aureus (39)(40)(41). We found that the presence of both SR-A and TLR-2 is required for the optimal phagocytosis of S. aureus by BDCA1 ϩ mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…The function of SR-A in human and mouse DCs and macrophages in response to Gram-negative and Gram-positive bacteria has been investigated, showing that SR-A functionally contributes to phagocytosis of those bacteria (37,38). Moreover, many studies showed that SR-A plays a significant role in the phagocytosis of S. aureus (39)(40)(41). We found that the presence of both SR-A and TLR-2 is required for the optimal phagocytosis of S. aureus by BDCA1 ϩ mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF enhances expression of scavenger receptors SR-A and MARCO (Sulahian et al, 2008; Szeliga et al, 2008) which may modify host resistance to viral infection (DeWitte-Orr et al, 2010; Mukhopadhyay et al, 2011). SR-A modifies inflammatory responses via the SP-A receptor SP-R210 (Sever-Chroneos et al, 2011). Mean survival from influenza infection between SR-A −/− and WT mice were similar (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar macrophages isolated by lung lavage were processed, stained, and analyzed by flow cytometry as described in detail previously (Sever-Chroneos et al, 2011). Briefly, cells were stained with monoclonal PE/Cy5-conjugated CD11c antibody clone N418 (eBiosciences, San Diego, CA), rabbit polyclonal SP-R210/Myo18A antibody (Protein-Tech, Chicago, IL), and a goat polyclonal anti-SR-A/Msr1 antibody (R&D Systems, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…The arrows within the photomicrograph indicate nuclear localization of NF-kB-p65. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] regions of SP-A that bind to TLR4 and modulate immune responses.…”
Section: Discussionmentioning
confidence: 99%